Peran Parental Attachment Terhadap Perkembangan Agama dan Moral Anak Usia Dini - Utami Kumala Dewi; Raden Rachmy Diana (Jurusan PIAUD IAIN Syekh Nurjati Cirebon, 2023)
ABSTRACT Parents become role models for growth and development in children's daily lives. The contribution of parents as an effort to motivate, guide, stimulate and provide facilities in order to achieve the ideals of child development. The term parental attachment is also called attachment between parents and children which is very important in growth and development, so that positive energy is created for children. Religious and moral development is very important to be formed from an early age such as tolerance, honest behavior, courtesy and responsibility. Forming positive characters through religion and morals, with the hope of forming a generation that is moral, religious and dignified. Therefore, researchers are interested in studying more deeply about how parental attachment is to religious and moral development at RA DWP UIN Sunan Kalijaga Yogyakarta. The method used by researchers is a descriptive qualitative method. The results of this study, in the form of implementing parents and children's attachment at home, through the distribution of open questionnaires in the form of descriptions.Keywords: The Role of Parental Attachment, Religious and Moral Development, Early Childhood